A genome-wide association study identifies a novel locus on chromosome 18q12.2 influencing white cell telomere length. Issue 7 (8th April 2009) - Mangino, M; Richards, J B; Soranzo, N; Zhai, G; Aviv, A; Valdes, A M; Samani, N J; Deloukas, P; Spector, T D
Abstract : Background: Telomere length is a predictor for a number of common age related diseases and is a heritable trait. Methods and results: To identify new loci associated with mean leukocyte telomere length we conducted a genome wide association study of 314 075 single nucleotide polymorphisms (SNPs) and validated the results in a second cohort (n for both cohorts combined = 2790). We identified two novel associated variants (rs2162440, p = 2.6×10 −6 ; and rs7235755, p = 5.5×10 −6 ) on chromosome 18q12.2 in the same region as the VPS34/PIKC3C gene, which has been directly implicated in the pathway controlling telomere length variation in yeast. Conclusion: These results provide new insights into the pathways regulating telomere homeostasis in humans.